Measuring and analyzing the effectiveness of monetary and financial policies towards the Iraqi Iranian trade exchange by using the model (ARDL) for duration (20042018) - Jalil Abdulhasan, Abdulhussein; Sharif Neaem, Hussein (International Journal of Psychosocial Rehabilitation, 2020)
After 2003, the Iraqi economy had many of the changes in the systems and policies, but economic manifested most important in shaping an independent monetary policy through legislation Law No. ( 56) for a year 2004M , while experienced a financial sentence policy shifts in legal legislation and in line with the external openness and financial liberalization of oil revenues from the UN sanctions , but these changes are not accompanied by a clear vision and milestones in development planning and building the economy of a real based on the self , it which was reflected in the high degree of exposure of trade towards the outside world and enhanced the race between the partners trade to acquire the Iraqi market who saw In his window to dispose of their products, including Iran.